2-Aryl-5-amino-1, 2, 3-triazoles: New effective blue-emitting fluorophores. (January 2017) - Gavlik, Kseniya D.; Sukhorukova, Ekaterina S.; Shafran, Yuri M.; Slepukhin, Pavel A.; Benassi, Enrico; Belskaya, Nataliya P.
Abstract: The synthesis of a new series of 2-aryl-5-amino-1, 2, 3-triazole derivatives is reported. The photochemical properties of these new fluorophores were studied both experimentally and using theoretical models. The compounds were found to be fluorescent, with Stokes shifts ranging from 40 nm (2494 ≿м −1 ) to 140 nm (9461 cm −1 ) and quantum yield values between 0.004 and 0.996. The fluorescence of the 1, 2, 3-triazoles was highly structure dependent and could be tuned by variation of the substituents at the C-4 and C-5 atoms of triazole ring and by the electronic and spatial effect of substituents within the aromatic cycle. Photophysical studies showed moderate changes in the fluorescence quantum yields depending on the solvent polarity. The UV–Vis spectra calculations employing the time-dependent density functional theory (TD-DFT) are in good agreement with the experimental data. The favourable photophysical properties of the studied compounds and their facile and high-yielding synthesis make them excellent candidates for commercial application as fluorescent tags. Graphical abstract: Highlights: One-pot synthesis of a series of new 2-aryl-5-amino-1, 2, 3-triazole derivatives. Experimental and computational approaches to optical properties correlate well. High photoluminescence quantum yield (99.6%) was achieved. Fluorescent properties can be tuned varying the substituents in 1, 2, 3-triazoles.